The stratification aspect of the formation of the image of the enemy: ascending and descending vectors of dehumanization in the social structure - D. A. Lushnikov (Современная наука и инновации)
The problems of dehumanization and the formation of the image of the enemy in a stratified society are considered. The vertical aspect of dehumanization involves the dehumanization of an individual/group located at a different level of the social hierarchy, so this process has an ascending and descending vector. The downward vector of dehumanization involves the infrahumanization and dehumanization of individuals/groups occupying a lower position in the social structure of society. The ascending vector of dehumanization implies infrahumanization and dehumanization of individuals/groups occupying a higher position in the social structure of society.